Self-Objectification among University students of Lahore: Beauty Vlogs, Parents’ Involvement & Societal Pressure as Predictors - Zahra, Sadaf; Saleem, Dr. Noshina (Journal of Peace, Development and Communication, 2021)
This research study patently aimed to examine the relationship between beauty vlogs’ body ideals and self-objectification among students. Assessing the role of parents’ involvement and societal pressure as predictors was however another prime objective of the study. For this purpose, students enrolled in two public and two private sector universities were selected as population and using convenience sampling technique, 600 students i.e. 150 respondents from each university was taken as sample of the study. Similarly, cross-sectional survey method was used for data collection whereas Pearson product moment, multiple linear regression and one-way ANOVA were applied for the analysis. Results of the study evidently found that though media exposure and family involvement also played their role but societal pressure was the major predictor and it contributed a lot to get the students inclined towards self-objectification.